Inhibition of alpha-L-fucosidase by derivatives of deoxyfuconojirimycin and deoxymannojirimycin. - Winchester, B; Barker, C; Baines, S; Jacob, G; Namgoong, S; Fleet, G (1990)
Deoxyfuconojirimycin (1,5-dideoxy-1,5-imino-L-fucitol) is a potent, specific and competitive inhibitor (Ki 1 x 10(-8) M) of human liver alpha-L-fucosidase (EC 3.2.1.51). Six structural analogues of this compound were synthesized and tested for their ability to inhibit alpha-L-fucosidase and other human liver glycosidases. It is concluded that the minimum structural requirement for inhibition of alpha-L-fucosidase is the correct configuration of the hydroxy groups at the piperidine ring carbon atoms 2, 3 and 4. Different substituents in either configuration at carbon atom 1 (i.e. 1 alpha- and beta-homofuconojirimycins) and at carbon atom 5 may alter the potency but do not destroy the inhibition of alpha-L-fucosidase. The pH-dependency of the inhibition by these amino sugars suggests very strongly that inhibition results from the formation of an ion-pair between the protonated inhibitor and a carboxylate group in the active site of the enzyme. Deoxymannojirimycin (1,5-dideoxy-1,5-imino-D-mannitol) is also a more potent inhibitor of alpha-L-fucosidase than of alpha-D-mannosidase. This can be explained by viewing deoxymannojirimycin as beta-L-homofuconojirimycin lacking the 5-methyl group. Conversely, beta-L-homo analogues of fuconojirimycin can also be regarded as derivatives of deoxymannojirimycin. This has permitted deductions to be made about the structural requirements of inhibitors of alpha- and beta-D-mannosidases.